2003
DOI: 10.1002/cncr.11162
|View full text |Cite
|
Sign up to set email alerts
|

Extraskeletal myxoid chondrosarcoma

Abstract: These findings supported the role of wide excision in the local control of EMC, irrespective of the previous excision procedure or recurrence. The protracted clinical course of the tumors and the presence of patients who had distant metastasis develop after definitive surgery of the primary tumor represented EMC as intermediate malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(49 citation statements)
references
References 27 publications
6
42
0
1
Order By: Relevance
“…Patients with EMC follow a protracted clinical course with a relatively high incidence of distant spread, typically to the lung,[15] and poor response rates to most conventional chemotherapeutic agents. [16] In one of the larger clinicopathologic studies to date including 42 patients with EMC, the overall survival was 100% at 5 years and 69% at 10 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with EMC follow a protracted clinical course with a relatively high incidence of distant spread, typically to the lung,[15] and poor response rates to most conventional chemotherapeutic agents. [16] In one of the larger clinicopathologic studies to date including 42 patients with EMC, the overall survival was 100% at 5 years and 69% at 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…[16] In one of the larger clinicopathologic studies to date including 42 patients with EMC, the overall survival was 100% at 5 years and 69% at 10 years. [15] The correlation between histologic grade in EMC and behavior has been controversial. Most cases of EMC are predominantly myxoid, with low cellularity and classified as low grade tumors.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Kawaguchi et al present data to support the role of a wide local excision due to a high rate of local recurrence. [7] Chondrosarcomas are notoriously resistant to conventional chemotherapy and radiation treatments, making curative resection the only definitive cure. In advanced or metastatic tumors, recent studies with novel chemotherapy regimens have not demonstrated increased survival.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its high tendency to local recurrences and distant metastases, it has a relatively slow growth and a lazy clinical course [12, 13]. …”
Section: Discussionmentioning
confidence: 99%